An Interdisciplinary Review of Dental Pharmacotherapy and Its Role in Oral Health - Hunidel Saleh Aljammaz,; WejdanAtiah AlHarthi,; Nahaia Mohammed Alnaiem,; Aminah Fazaa Alanazi,; Abdullah Mohammd M Aljeaid,; Amnah Nashi Bnai Alrashidi,; Nadia Bakhit Sorour Al-Rashidi,; Tahani Menawer Alzabni,; Abdullah Ahmad Salem Al Qarni,; Mansour Omar M Al saab,; Mohammed Abdullah alelweet, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study presents an interdisciplinary review of dental pharmacotherapy and its integral role in promoting oral health, utilizing an extensive analysis of secondary data sources. The increasing complexity of dental conditions necessitates a comprehensive understanding of pharmacological interventions to improve patient outcomes. By examining existing literature, databases, and prior research studies, this review elucidates the efficacy, safety, and application of pharmacological treatments in dentistry. Diverse therapeutic classes, including antibiotics, analgesics, and anti-inflammatory drugs, are evaluated in the context of specific dental pathologies and patient demographics. The study also explores the synergy between pharmacotherapy and other treatment modalities, highlighting advancements in drug formulations and delivery systems. Emphasis is placed on the interdisciplinary collaboration among dental professionals, pharmacists, and healthcare providers to optimize therapeutic strategies and ensure evidence-based practice. Challenges such as drug resistance, interactions, and patient adherence are discussed, alongside regulatory considerations and emerging trends in dental pharmacology. This comprehensive review underscores the pivotal role of pharmacotherapy in enhancing oral health and the importance of continued research to refine and expand its applications in dental care.